68 Effects of Intranasal or Parenteral Respiratory Vaccination Administered on Arrival or Delayed in Auction-derived Feedlot Heifers. (8th October 2021) - McAllister, Hudson; Halsted, Sherri; Parks, Tim; Streeter, Marshall N; Hutcheson, John P; Richeson, John
Abstract: Modified-live virus (MLV) vaccines are used routinely to immunize cattle against bovine respiratory disease (BRD) agents, but differences in the route and timing of MLV administration may exist. The objective was to evaluate the safety and efficacy of a parenteral or intranasal MLV administered on d 0 or 28. Three truckload blocks of heifers (initial BW=208 kg; n = 600) were randomly assigned to treatments in a 2×2 factorial. The generalized complete block design consisted of 15 pens/treatment with pen as the experimental unit and 10 animals/pen. Treatments were: 1) Nasalgen 3/Vista BVD CFP on d 0 (NAS0); 2) Vista 5 SQ on d 0 (VIS0); 3) Nasalgen 3/Vista BVD CFP on d 28 (NAS28); 4) Vista 5 SQ on d 28 (VIS28). Performance, activity, and health data were analyzed in a mixed model and a subset of 3 cattle/pen were selected for antibody titer analyses with repeated measures. Body weight and blood samples were collected on d 0, 28, and 56. No differences existed for performance outcomes (P ≥ 0.19). Activity (351.4 vs. 354.3 min/d) and rumination (282.6 vs. 285.4 min/d) time was less (P < 0.01) for delayed vs. arrival vaccinated heifers. A timing × vaccine × day interaction existed (P < 0.01) for IBRV-specific antibody titers such that VIS0 was greatest, NAS0 was intermediate, and VIS28 and NAS28 were least on d 28 (P < 0.01). Percentage of chronically ill cattle was reduced for arrival vs. delayed (1.3 vs. 4.7%; P = 0.02) and tended (P = 0.06) to be less for VIS vs. NAS (1.7 vs. 4.3%). Arrival vaccinated heifers had a reduction in antimicrobial treatment cost (4.63 vs. 7.31; P = 0.02). These data indicate improvement in some health outcomes for the parenteral route and arrival timing of MLV respiratory vaccination but performance was not affected.